Paget's disease of bone. Issue 4 (August 2018) - Fishlock, Adelle; Patel, Neelam
Abstract: Paget's disease of bone is a bone modelling disorder, characterized by skeletal deformity. Although the aetiology is largely unknown, environmental and genetic theories have been proposed. Serum alkaline phosphatase and plain radiographs remain the most commonly utilised investigations for diagnosis, and allow monitoring of the disease process. Second-generation bisphosphonates continue to be the mainstay of treatment, but surgical intervention may be required to treat complications including fracture, deformity and arthritis. This article reviews the epidemiology, aetiology, clinical features, investigations and treatment, including both medical and novel surgical options.